Application of polypropylene mesh in patient with recurrent femoral head dislocation after total hip arthroplasty (case from practice) - Golovakha, Maksim; Maslennikov, Sergey; Tverdovsky, Anatoliy; Zabielin, Ivan; Krasnoperov, Sergey; Banit, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
One of complications after total hip arthroplasty is femoral head dislocation. It occurrence in case of primary replacement can happen from 0,2 till 2 %. In such cases after primary dislocation and close reduction recurrence can happen in 16–59 %. In this article we present clinical case of the treatment of recurrent femoral head luxation after total hip arthroplasty. Patient had two revision surgeries, defect of hip joint capsule and ligaments was revealed, and this defect was replaced by polypropylene mesh implant during the last revision. There were not complications in postoperative period. On follow-up X-rays in 8 years there was full restoration of hip joint function (flexion more than 90°, abduction to 30°) and ability to walk. There was not recurrent head dislocation. Presented method of treatment reflects possibilities of modern medicine. Patient’s recovery — is the result of timely and qualified chosen methods of conservative and surgical treatment. Application of polypropylene mesh to close soft tissues defect in case of femoral head dislocation is discussion question. But our experience, absence of infection complication and recurrent dislocation can testify of a positive result.